Comentarios acerca de la evolución geológica del alto catatumbo (1995)
This paper presents   a brief analysis of the magmatism in the upper basin of the Catatumbo river, with special reference to a magmatic event whose deposits have characteristics which suggest that it took place during the cenozoic.  A resume of the tectonics of the upper Catatumbo basin, and its relations and geological similarities with the Bucaramanga region are also included.